Correlation between Ankle-Brachial Index Score and Diabetic Polyneuropathy Degree of Severity (Majalah Kedokteran Bandung, 2019)
Diabetic polyneuropathy (DPN) is the most prevalent chronic microvascular complication of type 2 diabetes mellitus (DM). The severity of DPN is categorized based on symptoms, signs, and nerve conduction study (NCS) abnormality into grades 0, 1a, 2a, and 2b. Pathogenesis of DPN consists of metabolic and vascular processes. In addition, macrovascular factor also plays a role in the pathogenesis of DPN. Macrovascular diseases, such as peripheral arterial disease (PAD), could be diagnosed using the ankle brachial index (ABI). Several studies have proven a strong correlation between ABI and DPN; hence, this study aimed to examine the correlation between ABI score and DPN severity. This was a cross sectional analytic study on. 73 type 2 DM patients who met the inclusion and exclusion criteria and visited the outpatient Endocrine Clinic and Neurophysiology laboratory of the Department of Neurology Dr. Hasan Sadikin General Hospital Bandung, during the priod of June to October 2018. ABI examination were performed after DPN indication was evident from results of physical examination, lab tests, and NCS. Rank Spearman statistical analyses were performed to assess the correlation between ABI score with DPN severity and the result was considered significant if p value
Keywords: Ankle brachial index; diabetic polyneuropathy; nerve conduction study